Potential for solar thermal energy in the heap bioleaching of chalcopyrite in Chilean copper mining. (January 2017) - Murray, Clare; Platzer, Werner; Petersen, Jochen
Highlights: Solar heating of heap leach liquor can boost heap leach performance. Combination of solar thermal and sulphide heap leach models to explore optimal configuration. Significant improvement of Cu recovery with a relatively small field of solar collectors. Positive NPV and good IRR for including solar heating of a sulphide under optimal conditions. Abstract: Bioleaching of chalcopyrite is only possible in the presence of thermophilic micro-organisms. While suitable conditions can be generated within a heap naturally through the exothermic reaction, the effectiveness of the process can be improved with an additional heat source. Chilean copper mines are primarily located in the Atacama Desert, which has the highest solar irradiation levels on the planet. Solar thermal energy can be incorporated into the heap bioleaching process to raise the temperature in the heap and increase the copper extraction rates. A heap bioleaching system, including ponds and a solar thermal collector field, has been simulated over one year using HeapSim and TRNSYS. The maximum copper extraction achievable for the system without a solar thermal field is 67% with a 7 kg/h m 2 solution flow rate. A maximum extraction of 85% over one year could be achieved with a collector field to heap area ratio of 1:1 and a 10 kg/h m 2 solution flow rate. An economic analysis compares the capital cost of the solar thermal system to the revenue from additional copper extraction. The net present value and internal rate of return were positive for collector areas in the range of 10, 000–150, 000 m 2 for a heap area of 200, 000 m 2 . The peak NPV occurs at 50, 000 m 2 at which point an extractionof 76% is achieved over one year of leaching.